Facilitators and Barriers to Healthy Eating Among American Indian and Alaska Native Adults with Type 2 Diabetes: Stakeholder Perspectives. (14th May 2021) - Stotz, Sarah A; Brega, Angela G; Gonzales, Kelly; Hebert, Luciana E; Moore, Kelly R; ,
ABSTRACT: Background: American Indian and Alaska Native (AI/AN) adults have a higher prevalence of type 2 diabetes (T2D) and related complications than non-AI/AN adults. As healthy eating is a cornerstone of diabetes self-management, nutrition education plays an important role in diabetes self-management education. Objective: To understand stakeholder perspectives on facilitators and barriers to healthy eating for AI/AN adults with T2D in order to inform the cultural adaptation of an existing diabetes nutrition education curriculum. Methods: Individual interviews were conducted with 9 national content experts in diabetes nutrition education (e.g. registered dietitians, diabetes educators, experts on AI/AN food insecurity) and 10 community-based key informants, including tribal health administrators, nutrition/diabetes educators, Native elders, and tribal leaders. Four focus groups were conducted with AI/AN adults with T2D ( n  = 29) and 4 focus groups were conducted with their family members ( n  = 22). Focus groups and community-based key informant interviews were conducted at 4 urban and reservation sites in the USA. Focus groups and interviews were recorded and transcribed verbatim. We employed the constant comparison method for data analysis and used Atlas.ti (Mac version 8.0) to digitalize the analytic process. Results: Three key themes emerged. First, a diabetes nutrition education program for AI/ANs should accommodate diversity across AI/AN communities. Second, it is important to build on AI/AN strengths and facilitators to healthy eating (e.g. strong community and family support systems, traditional foods, and food acquisition and preparation practices). Third, it is important to address barriers to healthy eating (e.g. food insecurity, challenges to preparation of home-cooked meals, excessive access to processed and fast food, competing priorities and stressors, loss of access to traditional foods, and traditional food-acquisition practices and preparation) and provide resources and strategies for mitigating these barriers. Conclusions: Findings were used to inform the cultural adaptation of a nutrition education program for AI/AN adults with T2D. Abstract : To understand key stakeholder perspectives regarding facilitators and barriers to healthy eating for American Indians with type 2 diabetes to inform the cultural adaptation of a diabetes nutrition education program.